2003
DOI: 10.1021/ja0289402
|View full text |Cite
|
Sign up to set email alerts
|

Copper Ion-Induced Activation and Asymmetric Benzoylation of 1,2-Diols:  Kinetic Chiral Molecular Recognition

Abstract: New catalytic ability of copper(II) ion has been exploited for monobenzoylation of 1,2-diols. The catalyst can be readily modified by ligation to acquire higher stereoselectivity. Highly effective kinetic resolution of dl-1,2-diols was achieved. The enantiodiscrimination process was clearly shown to be controlled by the kinetics of acylation of dl-1,2-diols. The catalytic method was successfully applied to asymmetric desymmetrization of meso-hydrobenzoin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
92
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(95 citation statements)
references
References 20 publications
1
92
0
2
Order By: Relevance
“…More specifically, developing environment-friendly, convenient, efficient and highly regioselective carbohydrate protection methods remains as one of the most prominent challenges [9]. Over the last several decades, many protection methods have been developed, including the use of reagents such as organotin [10][11][12], organoboron [13,14], organosilicon [15][16][17], metal salts [18][19][20][21][22][23], organobase [24][25][26], and enzymes [27][28][29][30]. Although these reagents each have advantages, they also possess troublesome shortcomings including inherent toxicity, high cost and the necessity to pre-protect secondary hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, developing environment-friendly, convenient, efficient and highly regioselective carbohydrate protection methods remains as one of the most prominent challenges [9]. Over the last several decades, many protection methods have been developed, including the use of reagents such as organotin [10][11][12], organoboron [13,14], organosilicon [15][16][17], metal salts [18][19][20][21][22][23], organobase [24][25][26], and enzymes [27][28][29][30]. Although these reagents each have advantages, they also possess troublesome shortcomings including inherent toxicity, high cost and the necessity to pre-protect secondary hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most frequently used protection methods is benzoylation. Many regioselective benzoylation methods using the above discussed reagents [20][21][22][25][26][27], have been reported accordingly. The Mitsunobu reaction is widely used in substitution of primary or secondary alcohols with nucleophiles mediated by a redox combination of a trialkyl or triarylphosphine and a dialkyl azodicarboxylate [31].…”
Section: Introductionmentioning
confidence: 99%
“…1 Although a multitude of enzymatic kinetic resolution methods have been developed for preparation of enantiomerically enriched -hydroxyalkanephosphonic acid derivatives, 2 to the best of our knowledge, nonenzymatic methods have not been reported. We recently reported an efficient method for kinetic resolution of 1,2-diols, 3 vic-amino alcohols, 4 and-or -hydroxyalkanamides 5 with copper(II) ion associated with chiral ligand (R,R)-Ph-BOX by acylation to obtain optically active alcohols with excellent enantioselectivity. 6 More recently, we have found that copper catalyst efficiently mediated kinetic resolution of-hydroxyalkanephosphonates.…”
Section: Introductionmentioning
confidence: 99%
“…The enantioselective desymmetrization of meso molecules is conceived to be another prospective means in the asymmetric transformation. So far, meso compounds have been mostly, if not all, desymmetrized to engender tertiary stereogenic centers (46)(47)(48)(49)(50)(51)(52)(53). It is of great value and significance to develop asymmetric desymmetrization creating chiral quaternary centers.…”
mentioning
confidence: 99%